Ökat hot och våld i arbetslivet – en följd av förändrade arbetsförhållanden? En studie utifrån de svenska Arbetsmiljöundersökningarna 1991–2005 (Sociologisk Forskning, 2009)
Increase in work related violence. A reflection of changes in working conditions? An analysis based on the Swedish Work Environment surveys.Victim surveys from Sweden show that the proportion reporting exposure to work related violence has increased. On the basis of the Swedish Work Environment surveys 1991–2005 this article focuses on the following questions: What kind of situations and working conditions are related to workplace violence? And, has the number of employees exposed to these working conditions increased parallel to the rise of reported workplace violence? Logistic regression analysis shows that some situations and working conditions are indeed related tothe risk of violence. To some extent exposure to these working conditions co-varies with exposure to violence. This result is more prominent for women than for men. Further research is needed to understand how changes in working conditions affect the risk of violence and the development thereof, not least from a gender perspective. Even so, changes in working conditions can not alone explain the increase of reported workplace violence in Sweden during this period. It seems that the influence of changed working conditions offers an interesting complement to criminological theories of broadened definitions and decreasing tolerance against violence in problematizing how an increase in reported workplace violence should and could be understood.